Studi Kasus Implementasi Metode Lean Startup pada UMKM Industri Makanan “MEN” - Maria Yvonne Hidajat; Lamtiur Hasianna Tampubolon; Heru Prasadja (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
In the era of rapid technological developments, companies are increasingly required to compete in goods and services markets more efficiently and effectively. Therefore choosing the most fit entrepreneurial method will play an important role in the sustainability and success of the company. One entrepreneurial method that is currently starting to get attention in the business world is the Lean Startup method. This research examines the description of Lean Startup method implementation in food catering MSME company